2011
DOI: 10.1007/s12522-011-0099-0
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms of various types of oocyte aging

Abstract: It is well established that age-related decline of a woman's fertility is related to the poor developmental potential of her gametes. The age-associated decline in female fertility is largely attributable to the oocyte aging caused by ovarian aging. Age-associated oocyte aging results in a decrease in oocyte quality. In contrast to ovarian aging, there is a concept of postovulatory oocyte aging. Postovulatory aging of oocytes, not being fertilized for a prolonged time after ovulation, is known to significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 165 publications
(229 reference statements)
1
19
0
Order By: Relevance
“…Postovulatory oocyte aging is classified into two types: in vivo ‐ and in vitro ‐postovulatory oocyte aging. If fertilization does not occur during the optimal period after ovulation, an unfertilized oocyte that remains in the oviduct ( in vivo ‐postovulatory oocyte aging) or in vitro culture ( in vitro ‐postovulatory oocyte aging) goes through a time‐dependent aging process . We and numerous other investigators have reported that in vivo‐ and in vitro ‐aged oocytes frequently show lower fertilization and blastocyst formation rates (Fig.…”
Section: Effects Of Postovulatory Oocyte Aging On Female Reproductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Postovulatory oocyte aging is classified into two types: in vivo ‐ and in vitro ‐postovulatory oocyte aging. If fertilization does not occur during the optimal period after ovulation, an unfertilized oocyte that remains in the oviduct ( in vivo ‐postovulatory oocyte aging) or in vitro culture ( in vitro ‐postovulatory oocyte aging) goes through a time‐dependent aging process . We and numerous other investigators have reported that in vivo‐ and in vitro ‐aged oocytes frequently show lower fertilization and blastocyst formation rates (Fig.…”
Section: Effects Of Postovulatory Oocyte Aging On Female Reproductionmentioning
confidence: 98%
“…There are several problems associated with the study of oocyte aging with respect to ovarian aging: it takes more than 1 year to obtain experimental animals that are old enough, and there are only a few available oocytes. Moreover, there is no appropriate animal model analogous to the one that is used in ovarian aging studies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takahashi et al . () reviewed two categories of oocyte ageing caused by ovarian ageing or post‐ovulatory ageing. The authors concluded that both categories of oocyte ageing have similar phenotypes of reproductive failure.…”
Section: Cellular Changes During the Progress Of Oocyte Ageingmentioning
confidence: 99%
“…Female infertility is exacerbated by socioeconomic changes in developed countries, which enable women to progressively delay the age at which they have their first child. As a consequence, there is increased demand for the treatment of infertility (3).…”
mentioning
confidence: 99%